Bodies and Documents: The Material Impact of Collaborative Information- Sharing Within the Seasonal Agricultural Worker Program - Clause, Courtney Jane (Frontiers in Communication, 2021)
This study examines information-sharing practices within the Seasonal Agricultural Worker Program (SAWP), focusing on the program as it is administered within Ontario. I analyze 61 documents for their content, codification of stakeholder relationships, and discourse regarding the program. Documents were selected based on their creation, use, or circulation within Ontario, and based on the likelihood that at least one stakeholder group would look to the document for (what they perceive to be) reliable information. Documents include, for example, SAWP contracts, webpages describing program requirements, and e-pamphlets on workplace safety and accessing services. Document analysis was supplemented by interviews with industry and service provider experts, which guided interpretation of documents’ significance. I argue that documents function as material actors, alongside (and sometimes beyond) human actors, and make physical impact on SAWP bodies and realities. Documents construct and uphold neoliberal structures surrounding the program by contributing to the creation and sustaining of incomplete, labour-centric individuals. Through consistent sharing of narrow, ‘work’ information, and the rare inclusion of more well-rounded, ‘non-work’ knowledge, documents subtly discipline the boundaries of acceptable and unacceptable communication. In doing so, material actors (alongside other SAWP actors) perpetuate a foreign worker program which does not consider the varied, complex needs of whole persons but, instead, treats them as disposable labouring bodies.